Mean Epidermal Thickness from Different Regions of Skin of Human Fetuses of 11-40 Weeks of Gestational Age: A Histometric Study - Dhingra, Shivani; Asghar, Adil (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Background: The estimation of fetal epidermal thickness has clinical significance for dermatological investigation and diagnosis of fetal prematurity. Objective: We aimed to collect baseline data of fetal epidermal thickness and secondarily to study the correlation of gestational age (GA) from epidermal thickness. Materials and Methods: Thirty fetuses were selected for the study aged from 11 to 40 weeks. They were divided into six groups at a 4-week interval. The mean epidermal thickness was measured at four sites such as the abdomen, interscapular region, scalp, and palm. The histometric analysis was done with the help of amscope 5MP Aptina MT9P001. Results: The mean age of gestation was 25.67 ± 8.45 weeks. The mean epidermal thickness of the abdominal, interscapular, scalp, and palmar region was 21.9 ± 12.9 µm (3.41–42.48), 111.21 ± 74.39 µm (7.9–214.51), 27.58 ± 13.26 µm (11.7–46.2), and 139.73 ± 96.40 µm (7.3–280.51), respectively. The growth pattern of the epidermis of the different region was significantly variable based on the ANOVA (P = 1.98E-13 P < 0.05 significant) and paired t-test of interregional comparison. Conclusions: The epidermal thickness has a significant positive correlation with GA and anatomical sites. We emphasize that epidermal thickness is a newborn maturity marker at birth.